La biblioteca de babel memoria y tecnología - Cuadra Rojas , Álvaro (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
In this article we propose a reflection about technology, emphasized the complexity of the phenomenon more than any determinism of causes and effects. Our heuristic construction proposes five categories basic in order to think the technological thing about Latin America: sign, time, reality, knowledge, power. Conscious of its precarious character, this pentagram allows us to articulate basic a categorial cross-linking in order to grasp an evasive and evanescent phenomenological field, that, however, one settles in the contemporary societies as an evidence, our tecnocultural surroundings happened memory.